2022
DOI: 10.1111/jocn.16190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alarm fatigue of nurses working in the COVID‐19 Intensive Care Service: A mixed methods study

Abstract: Aims and Objectives To reveal the existence of alarms in COVID‐19 intensive care units, where medical devices with alarm function are frequently used, the effects of alarms on nurses, especially their on‐the‐job performances and social lives, and their coping methods. Methodology/Methods This was a mixed design, including descriptive and qualitative research methods with two stages, and was carried out between March and April 2021. The study adhered to the STROBE checklist for cross‐sectional studies and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Torabizadeh et al [11] made the rst and so far the only attempt to systematically construct a reliable instrument for measuring alarm fatigue in nurses. Some studies, of which ve were peer-reviewed [12][13][14][15][16] and two were published as dissertation manuscripts [17,18], already used Torabizadeh et al's questionnaire, while others took it as a resource to build their own custom questionnaire [19]. We welcome this trend towards using a standardised, uniformly agreedupon instrument in clinical alarm research.…”
Section: Introductionmentioning
confidence: 99%
“…Torabizadeh et al [11] made the rst and so far the only attempt to systematically construct a reliable instrument for measuring alarm fatigue in nurses. Some studies, of which ve were peer-reviewed [12][13][14][15][16] and two were published as dissertation manuscripts [17,18], already used Torabizadeh et al's questionnaire, while others took it as a resource to build their own custom questionnaire [19]. We welcome this trend towards using a standardised, uniformly agreedupon instrument in clinical alarm research.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that although alarm fatigue is present, nurses in the intensive care unit still act by alarm management. In the study of Akturan et al 10 in which they evaluated the alarm fatigue of nurses working in COVID-19 intensive care units, they stated that nurses were more sensitive to the alarms of some patients whose clinical condition worsened and to the alarms of some devices during night shifts (such as being more sensitive to mechanical ventilators than to the sound of the infusion pump). It has also been suggested that nurses who work overtime and are less active on the night shift compared to the day shift may cause them to hear alarms more and react negatively.…”
Section: Discussionmentioning
confidence: 99%
“…"The heavy workload in some shifts prevents my quick response to alarms" 66.6% of the participants answered this question as heavy workload sometimes-usuallyalways prevents them from responding to alarms. In the study of Akturan et al 10 "the necessity to wear personal protective equipment" was determined as a factor that increases alarm fatigue in a process such as a pandemic where workload increases. The international patient safety commission has made some recommendations by setting targets for 'Improving Clinical Alarm Systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations